TMV nanorods with programmed longitudinal domains of differently addressable coat proteins - Geiger, Fania; Eber, Fabian Johannes; Eiben, Sabine; Mueller, Anna; Jeske, Holger; Spatz, Joachim P.; Wege, Christina (Nanoscale, 2013)
The spacing of functional nanoscopic elements may play a fundamental role in nanotechnological and biomedical applications, but is so far rarely achieved on this scale. In this study we show that tobacco mosaic virus (TMV) and the RNA-guided self-assembly process of its coat protein (CP) can be used to establish new nanorod scaffolds that can be loaded not only with homogeneously distributed functionalities, but with distinct molecule species grouped and ordered along the longitudinal axis. The arrangement of the resulting domains and final carrier rod length both were governed by RNA-templated two-step in vitro assembly. Two selectively addressable TMV CP mutants carrying either thiol (TMVCys) or amino (TMVLys) groups on the exposed surface were engineered and shown to retain reactivity towards maleimides or NHS esters, respectively, after acetic acid-based purification and re-assembly to novel carrier rod types. Stepwise combination of CPCys and CPLys with RNA allowed fabrication of TMV-like nanorods with a controlled total length of 300 or 330 nm, respectively, consisting of adjacent longitudinal 100-to-200 nm domains of differently addressable CP species. This technology paves the way towards rod-shaped scaffolds with pre-defined, selectively reactive barcode patterns on the nanometer scale.